Eu sou tu, tu és eu: Persona 4 e o gênero em jogo - Araújo, Guilherme Pedrosa Carvalho de (2021)
This dissertation aims to understand how the gender identity and sexual orientation of the characters in Persona 4 are constructed, based on the aesthetic, narrative and mechanical resources of a digital game. Therefore, were taken into account the development of the characters, the atmosphere of the game’s missions, the visual aspects and part of combat and strategy from the work in question. The main questioning on the concept of game was based on authors such as Huizinga (2003), Caillois (2001), McLuhan (2007) and Brougère (2003), and the approach of its digital form was guided by the contributions of Schell (2008), Crawford (1982), Adams (2010) and Isbister (2006), among others. To understand the concepts related to the gender studies, the propositions were based on authors such as Butler (2003), Louro (2000), Miskolci (2012), Federici (2018) and Wolf (2019), allied to the concept of characters taking as reference Seger (1990), Candido et al. (1997), Brait (1985) and Mungioli (2014), among others. Based on a qualitative approach, focusing this work’s efforts on five characters: Chie, Yukiko, Kanji, Rise and Naoto; we opted for the three-phase method of studying games proposed by Petry et al. (2013). As for the delimitation of the corpus, we worked with the concept of quests as episodic structures of digital games, based on the work of Howard (2008) and Oliveira and Massarolo (2010). With the analysis, we observed that despite using the resources of digital games widely, Persona 4 still uses outdated conceptions and metaphors for the formulation of its characters. If, on the one hand, the widespread use of aesthetic, narrative and mechanical elements allows a deeper understanding of gender issues related to the characters, on the other hand, the imprecise basis of some of these narratives strengthens the excluding and oppressive discourses in our society.